Distorted Input Ratios in Vertical Relationships. (26th November 2019) - Peitz, Martin; Shin, Dongsoo
Abstract: A project leader sources an input from a supporter and combines it with an input produced in‐house. The leader has private information about the project's cost environment. We show that if the leader can commit to the in‐house input level, the input ratio is distorted upward when the in‐house input is not too costly – the in‐house input is produced in excess and thus partly wasted. By contrast, without the leader's commitment to the in‐house input level, the input ratio is distorted downward when the in‐house input is sufficiently costly – the outsourced input is produced in excess and thus partly wasted.